Analisis Kerataan Jalan Menggunakan Nilai IRI pada Jalan Kolektor Kabupaten Tegal - Hadi, Suprapto; Saputra, Patrio (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2024)
Cut Nyak Dien Road is the main access that connects Tegal City and Tegal Regency so that it has a strategic role in supporting community mobility and economic activities. This section is included in the type of secondary collector road located in Tegal Regency, Central Java. This research discusses pavement surface damage on Jalan Cut Nyak Dien, Tegal City using the Hawkeye 2000 Series. The main focus is identifying road safety aspects such as road damage, signs, markings and IRI values. The method used includes the use of a Hawkeye 2000 Series car to collect road condition data. It is hoped that the research results will provide a clear picture of road surface regarding conditions and their IRI values so that they can provide concrete recommendations for the development of safer and more effective road infrastructure in Indonesia.